Mast Cell Stabilizing Activity of Ocimum Sanctum Leaves - GAJENDRA P. CHOUDHARY, (International Journal of Pharma and Bio Sciences, 2010)
The mast cell has long been associated with asthma, since it releases a variety of preformed and newly synthesized mediators that account for several features of asthma. Among the mediators, histamine is a wellcharacterized and the most potent vasoactive mediator in acute bronchoconstriction. In the present study, albino rats were sensitised by horse serum along with triple antigen containing Bordetella pertussis.Treatment was given with Ocimum sanctum ethanolic extract and flavonoid fraction and standard for 14 days. On the 14th day 3 hours after the last dose treatment, rats were sacrificed and intestinal mesentery taken out for study of mast cell. In the unsensitized rats, 12.55% of the mast cells were in the process of degranulation. In the sensitized untreated rats, 80.90% of the mast cells degranulated when challenged with the antigen. Prednisolone used as reference standard was found to inhibit degranulation of mast cells to an extent of 72.25%. The ethanolic extract at 100 and 200 mg/kg body weight inhibited degranulation of mast cells to an extent of 62.44 and 67.24%, respectively. Preliminary phytochemical analysis showed positive response for flavonoids.The isolated flavonoidal fraction of Ocimum sanctum at 75 and 150 mg/kg body weight inhibited degranulation of mast cell to an extent of 54.62 and 60.48% respectively.